An examination of technical, pure technical and scale efficiencies in GCC banking. (18th August 2008) - Al-Muharrami, Saeed
The paper uses DEA techniques to estimate technical, pure technical, and scale efficiency, using an input orientation for Gulf Cooperation Council (GCC) banks for the period 1993?2002. The paper highlighted several interesting findings regarding the GCC banking market. First, smaller banks exhibited superior performance in terms of overall technical efficiency than did larger ones. Second, big banks proved to be more successful in adopting the best available technology, while medium banks proved to be more successful in choosing optimal levels of output. Third, Islamic banks were more successful in both the adoption of the best available technology and choosing optimal levels of output. Fourth, banks in Bahrain, Qatar, Oman, UAE, Kuwait and Saudi Arabia ranked first to sixth, respectively, in terms of technical efficiency.